Relationship between hydrogeochemical characteristics of hot springs and seismic activity in the Jinshajiang fault zone, Southeast Tibetan Plateau - Liu, Jie; Zhou, Xiaocheng; Li, Ying; He, Miao; Li, Jingchao; Dong, Jinyuan; Tian, Jiao; Yan, Yucong; Ouyang, Shupei; Liu, Fengli (Frontiers in Earth Science, 2023)
Significant anomalous hydrogeochemical changes in hot spring water are detected during strong seismic cycles. It is now necessary to clarify the relationship between tectonic movements, earthquakes and the evolution of hot springs. In this paper, laboratory analyses of major, trace elements, δD, δ18O and 87Sr/86Sr values of 28 hot spring waters in the Jinshajiang fault zone (JSJFZ) in the northwestern boundary of the Sichuan-Yunnan block were conducted. The results showed that the primary source of water for JSJFZ hot springs was atmospheric precipitation. The geothermal reservoir temperature variation based on the silicon enthalpy mixing model ranged from 73 to 272◦C. And the circulation depth range was 1.2 to 5.4 km. The segmentation characteristics of the 87Sr/86Sr values were related to the influence of source rocks on groundwater cycle processes. A conceptual model of the hydrologic cycle of hot springs explained the spatial distribution of earthquakes associated with tectonic movements. The Batang segment had the strongest water-rock reaction, the highest reservoir temperature and the deepest circulation depth; meanwhile, it was also an earthquake prone area. The fluid circulation of the JSJFZ corresponds well with the seismicity, which indicates that the hydrological characteristics of the hot spring water in a fracture zone play a crucial role in receiving information on seismic activity.